Zero Triple Product Determined Matrix Algebras - Hongmei Yao; Baodong Zheng (Journal of Applied Mathematics)
Let A be an algebra over a commutative unital ring C. We say that A is zero triple product determined if for every C-module X and every trilinear map {⋅,⋅,⋅}, the following holds: if {x,y,z}=0 whenever xyz=0, then there exists a C-linear operator T:A3⟶X such that x,y,z=T(xyz) for all x,y,z∈A. If the ordinary triple product in the aforementioned definition is replaced by Jordan triple product, then A is called zero Jordan triple product determined. This paper mainly shows that matrix algebra Mn(B), n≥3, where B is any commutative unital algebra even different from the above mentioned commutative unital algebra C, is always zero triple product determined, and Mn(F), n≥3, where F is any field with chF≠2, is also zero Jordan triple product determined.